Experiential Learning Framework: Summary Guide - Gofton, Tyson; Ramsay, Gabriel (Université d'Ottawa | University of Ottawa, 2025)
The Experiential Learning (EL) Framework at the University of Ottawa is a practical and strategic tool designed to support program development, course design, and the recognition of high-quality EL activities. Originally developed as part of the creation of the In-depth Experiential Learning Stream (IELS), a 30-credit undergraduate stream of EL-labelled courses, the framework has since evolved into a broader institutional guide to enhance coherence, quality, and visibility across experiential offerings. As new forms of EL continue to be developed and implemented across campus, the framework itself will continue to evolve to support emerging needs and opportunities.
Keywords: Experiential Learning; Pedagogie; Curriculum Design; Work integrated learning; Community service learning; Competencies; Skills; CO-OP; Co-operative education